Contract-first web services six reasons to start with WSDL and schema. - Close, Steve (SOA webservices journal.)
I believe that there is a strong tendency for developers to think of Web services as methods. In reality it is not that simple. A Web service defines an XML conversation between client and server. Yet, when a developer sits down to create Web services he or she usually starts by creating a method.